Kosovo women's knowledge and awareness of human papillomavirus (HPV) infection, HPV vaccination, and its relation to cervical cancer - Pranvera Zejnullahu Raçi; Fitim Raçi; Teuta Hadri (BMC, 2021)
Abstract Background The objective of this study, the first of its kind in Kosovo, is to determine the level of Kosovo women's knowledge and awareness of HPV infection, HPV vaccination, and its relation to cervical cancer. Methods This cross-sectional study was conducted from July to October 2018 at the Clinic of Obstetrics and Gynecology at the Hospital and University Clinical Service of Kosovo. Results Out of 800 questionnaires distributed, 645 were completed and returned (80.6%). Only 0.5% of women were vaccinated against HPV. The majority of respondents (66.4%) had no previous knowledge of HPV (human papillomavirus). Only 27.6% of respondents were aware that HPV is responsible for cervical cancer. About two-thirds (70.1%) of respondents had never heard of the HPV vaccine, and only 24% knew that the HPV vaccine can prevent cervical cancer. Conclusion The level of vaccination against HPV and the level of knowledge and awareness of HPV infection is extremely low. Higher education, younger age, and living in an urban area were favorable factors and correlated with awareness of HPV infection, vaccination against it, and its relation to cervical cancer. Based on this study, there is an immediate need for developing an educational program on HPV infection and the importance of HPV vaccination as a preventative measure against developing cervical cancer.